A STUDY ON MASTERING ENGLISH TRANSITIVE VERBS BY THE GRADE 10 STUDENTS OF ENSINO SECUNDARIA GERAL 10 DE DEZEMBRO COMORO DILI - REIS, ANA JOANA DOS (Academic Journal of Educational Sciences, 2022)
The objectives of this study are to find out how far the grade 10 students of Ensino Secundaria Geral 10 de Dezembro Comoro-Dili master English transitive verbs and to know their ability level in mastering English transitive verbs. It applied qualitative and quantitative methods. The instrument used in this study was a written test consisting of twenty-five numbers, such as ten multiple choices, ten numbers filling in the gaps, and five numbers Essay test. The sample of this study was 30 selective students of grade 10 student of ensino Secundaria Geral 10 de Dezembro Comoro-Dili in the school year 2020. The results show that the students made 493 correct answers with 65.73%, 257 wrong answers with 34.27%, and there wa null for students' no answer. It can be concluded that the students were able to master English transitive verbs because the correct answers were higher than the wrong answers. However, the students were mostly categorized at the average level of mastering English transitive verbs, from 11 to 20 of total scores of 455 with a percentage of 99,2%. Finally, no students were categorized into the high level of mastering English transitive verbs, and seven students were categorized into the low level of mastering English transitive verbs. The scores range from 0-6 with 0.8%.